Pengembangan Desain Mesin CNC Router Skala Laboratorium Menggunakan Software Mach3 - Rasyid, Syaharuddin; Salam, Abdul; Ainul Yaqin, Muh; Hidayanti, linda; Prederick, Efrat (Jurnal Teknik Mesin Sinergi, 2025)
The goals of this CNC router machine development research are develop the control system for the CNC router using Mach3, improve product quality with a clamping system, increase the machine's production capacity from initially handling just one workpiece, and estimate the costs of developing the CNC router machine. The research stages include literature review, design (design & drawing), selection and procurement of mechanical and control materials, function and component compatibility checks, construction and assembly of mechanical and control systems, data analysis, and conclusions. Data collection methods involve using different materials, such as acrylic and MDF, and measuring the precision in product manufacturing. The research concludes that the control system development for the CNC router using Mach3 has been successful. The designed control system employs Nema 23 stepper motors as actuators and Mach3 as the CNC software. This system can control the CNC machine’s movement on the X, Y, and Z axes according to the input program. The use of clamps on the CNC router ensures the workpiece remains stationary, preventing errors in cutting or engraving. Additionally, using a stopper or workpiece placement device on the CNC router facilitates easier installation and quick workpiece replacement, thereby enhancing productivity.